2011
DOI: 10.2147/ijgm.s20875
|View full text |Cite
|
Sign up to set email alerts
|

Diurnal salivary cortisol concentrations in Parkinson’s disease: increased total secretion and morning cortisol concentrations

Abstract: Background:Parkinson’s disease (PD) is a chronic neurodegenerative disorder. There is limited knowledge about the function of the hypothalamic-pituitary-adrenal axis in PD. The primary aim of this prospective study was to analyze diurnal salivary cortisol concentrations in patients with PD and correlate these with age, gender, body mass index (BMI), duration of PD, and pain. The secondary aim was to compare the results with a healthy reference group.Methods:Fifty-nine PD patients, 35 women and 24 men, aged 50–… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
19
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 37 publications
0
19
1
Order By: Relevance
“…Similarly, elevated serum cortisol levels were reported in a larger collective study of idiopathic and non-idiopathic PD patients compared to controls ( 281 ). It is important to note that cortisol concentrations measured from saliva samples do not reflect any signs of pathology ( 282 ) and this should be a key consideration in the design of future clinical studies. While the inconsistencies between previous plasma profiling studies could be attributed to age, progression of disease or drug treatment, salivary cortisol levels appear to be unaffected by levodopa or dopamine agonist drug treatments ( 283 ), and do not correlate with duration of the disease and motor symptoms ( 282 ).…”
Section: Depression In Parkinson’s Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, elevated serum cortisol levels were reported in a larger collective study of idiopathic and non-idiopathic PD patients compared to controls ( 281 ). It is important to note that cortisol concentrations measured from saliva samples do not reflect any signs of pathology ( 282 ) and this should be a key consideration in the design of future clinical studies. While the inconsistencies between previous plasma profiling studies could be attributed to age, progression of disease or drug treatment, salivary cortisol levels appear to be unaffected by levodopa or dopamine agonist drug treatments ( 283 ), and do not correlate with duration of the disease and motor symptoms ( 282 ).…”
Section: Depression In Parkinson’s Diseasementioning
confidence: 99%
“…It is important to note that cortisol concentrations measured from saliva samples do not reflect any signs of pathology ( 282 ) and this should be a key consideration in the design of future clinical studies. While the inconsistencies between previous plasma profiling studies could be attributed to age, progression of disease or drug treatment, salivary cortisol levels appear to be unaffected by levodopa or dopamine agonist drug treatments ( 283 ), and do not correlate with duration of the disease and motor symptoms ( 282 ). Interestingly, one study reported that salivary cortisol levels could predict which PD patients were more likely to engage in risky behavior ( 284 ) and this could be an important consideration in the context of cognitive deficits or suicide ideation.…”
Section: Depression In Parkinson’s Diseasementioning
confidence: 99%
“…Parkinson's disease (PD) is a multifactorial complex disorder associated with motor signs as well as diverse nonmotor symptoms such as circadian disruption, depression, and cognitive decline. Dysregulation of the hypothalamic‐pituitary‐adrenal (HPA) axis, evidenced by hypersecretion of cortisol, is implicated in such nonmotor symptoms, and elevated levels of cortisol have been documented in PD, especially in the morning . Participation in physical activity may reduce the risk and rate of progression of PD, and endurance exercise may reduce the rate at which the signs of PD progress .…”
mentioning
confidence: 99%
“…Moreover, a decrease in the amplitude and total amount of melatonin and cortisol secretion has been observed [ 29 , 30 ]. In another study, the pattern of cortisol secretion was also blunted, but total cortisol concentrations were increased in PD subjects compared to healthy controls [ 31 ]. These changes in melatonin and cortisol secretion patterns have also been reported in non-PD subjects with a depressive disorder or insomnia [ 32 34 ].…”
Section: Introductionmentioning
confidence: 99%